The Midas formula - Clark, Malcolm; BBC worldwide ([London : BBC Worldwide, 1999)
The Black-Scholes formula changed the financial world forever. It could do the unthinkable. It took the risk out of investing in financial markets. To its inventors, it brought the Nobel Prize for Economics. For the people who used it, the Black-Scholes formula provided a means of making massive financial fortunes with a minimum of risk. Until it failed
Title from title screen
Narrator: Dilly Barlow
DVD format
Keywords: Stocks -- Mathematical models; Investments -- Mathematical models; Options (Finance) -- Mathematical models